The role of thyroid and steroid hormones in maturation of the adreline-sensitive reabsorptive mechanism of the fetal lung - Barker, Pierre M (Division of Clinical Pharmacology, 2018)
Around the time of birth, the lung switches from a secretory- to a liquid absorptive organ to enable the fetus to transit from an intra-uterine to an air-breathing environment. This study concerns hormonal control of the liquid reabsorptive mechanism in the fetal lung which allows this transition to take place. Thyroidectomy in the fetal sheep at 118 days gestation (term = 147 days) prevented the development of adrenaline- or cyclic AMP-sensitivity which, in euthyroid fetuses, resulted in the capacity to absorb lung liquid from 130 days onwards. Studies in which T₃ and T₄ were infused to thyroidectornized fetal sheep showed that T₃ was required for the normal evolution of the reabsorptive response. However, infusion of this hormone to immature fetuses (110 days) did not advance the gestation at which adrenaline-sensitive absorption is first seen. Co-infusion of T₃ and hydrocortisone showed that these 2 hormones have a powerful synergistic effect on the absorption mechanism. Within a few hours of infusion of these 2 hormones to immature fetuses, a reabsorptive response to adrenaline similar to that normally seen in mature fetuses was observed. This response was fully reversible on withdrawal of T₃ and hydrocortisone infusion, and the hormonal effect was blocked by the protein synthesis inhibitor, cyclohexirnide. These findings suggest that the normal rise in T₃ and cortisol seen in the fetus in late gestation is responsible for maturation of the liquid absorption mechanism which allows the fetus to make a transition to an independent air-breathing existence. These observations may be of significance in the clinical management of infants born prematurely, who may have had insufficient pre-natal exposure to T₃ and cortisol.